Growth and mortality parameters of Sillago sihama (Forsskal, 1775) in coastal waters of the Hormozgan Province, Iran - Safaie, Mohsen; Alizadeh, Roghayeh; Kamrani, Ehsan; Momeni, Mohammad (Indian Journal of Fisheries, 2016)
Monthly total length frequency data of silver sillago Sillago sihama were collected from the coastal waters of Hormozgan Province, Persian Gulf, from July 2011 to July 2012. ELEFAN-I module of FISAT II was used to analyse the length frequency data. The length-weight relationship derived, demonstrated that growth in this species is allometric. The asymptotic length (Lâˆž) was estimated as 26 and 30 cm for males and females, respectively. The growth parameter K was calculated asÂ 0.46 y-1 for males and 0.43 y-1 for females. The total mortality, natural mortality and fishing mortality rates estimated were: 3.55, 1.09 and 2.46 for males and 3.03, 1.00 and 2.03 for females, respectively. The exploitation rate E being more than 0.50, indicates S. sihama stock is currently being overexploited from the Persian Gulf.